Integrated immunogenicity analysis of a tetravalent dengue vaccine up to 4 y after vaccination - Claire Vigne; Martin Dupuy; Aline Richetin; Bruno Guy; Nicholas Jackson; Matthew Bonaparte; Branda Hu; Melanie Saville; Danaya Chansinghakul; Fernando Noriega; Eric Plennevaux (Taylor & Francis Group, 2017)
Two large pivotal phase III studies demonstrated the efficacy of the tetravalent dengue vaccine (CYD-TDV; Dengvaxia®, Sanofi Pasteur) against all dengue serotypes. Here we present an unprecedented integrated summary of the immunogenicity of CYD-TDV to identify the parameters driving the neutralizing humoral immune response and evolution over time. We summarized the immunogenicity profiles of a 3-dose schedule of CYD-TDV administered 6 months apart across 10 phase II and 6 phase III trials undertaken in dengue endemic and non-endemic countries. Dengue neutralizing antibody titers in sera were determined at centralized laboratories using the 50% plaque reduction neutralization test (PRNT50) at baseline, 28 d after the third dose, and annually thereafter for up to 4 y after the third dose in some studies. CYD-TDV elicits neutralizing antibody responses against all 4 dengue serotypes; geometric mean titers (GMTs) increased from baseline to post-dose 3. GMTs were influenced by several parameters including age, baseline dengue seropositivity and region. In the 2 pivotal studies, GMTs decreased initially during the first 2 y post-dose 3 but appear to stabilize or slightly increase again in the third year. GMTs persisted 1.2-3.2-fold higher than baseline levels for up to 4 y post-dose 3 in other studies undertaken in dengue endemic countries. Our integrated analysis captures the fullness of the CYD-TDV immunogenicity profile across studies, age groups and regions; by presenting the available data in this way general trends and substantial outliers within each grouping can be easily identified. CYD-TDV elicits neutralizing antibody responses against all dengue serotypes, with differences by age and endemicity, which persist above baseline levels in endemic countries.